The Hacienda System in Guanacaste Province, Costa Rica and the Creation of a labor force, 1880-1950. - Edelman, Marc, 1952-; Valverde Cháves, Jeannette; Columbia University (Estados Unidos); Department of Anthropology; Instituto de Investigaciones Sociales; Universidad de Costa Rica; 1982 National Meeting of the Latin American Studies Association. Panel S105 "Peasants, Wage Labor, and Commercial Agricultue in Turn-of-the-Century Latin America". Washington, DC March 3-6, 1982; Columbia University (Estados Unidos); Department of Anthropology; Insituto de Investigaciones Sociales; Universidad de Costa Rica (San José, CR : UCR; Instituto de Investigaciones Sociales, 1982)
Presenta la propuesta de trabajo para el quinquenio 2006-20011 de las candidatas para los puestos de decana y vice-decana de la Facultad de Ciencias Sociales de la UNA, Nelly López Alfaro (decana), y Jeannette Valverde Chaves (vice-decana).
Keywords: COSTA RICA; UNA; FACULTAD DE CIENCIAS SOCIALES; PLANES DE ACCION; PROGRAMAS DE TRABAJO; ARCHISO